Formation of The Practice-Oriented Educational Paradigm on The Basis of The Competence Approach - Gennadievna Nikitina, Marina; Viktorovna Pobirchenko, Viktoriya; Alekseevna Shutaieva, Elena; Georgievich Barsegyan, Ashot; Nikolaevich Dyatel, Vitaliy; Serverovich Abibullaev, Memet (Opción, 2019)
The article is devoted to the solution of the problem related to the formation of an integrated practice-oriented system of continuing education, which includes the realization of individual educational trajectories based on the competence approach. The study’s methodology is based on the methods of analysis and synthesis, induction and deduction. The study is based on the fundamental approaches to the development of education as an open multi- option system and to the individualization of the educational process as a prerequisite of the personal and professional formation of a specialist, as well as theoretical provisions about multi-functional pedagogical activities. It has been established that education based on individual educational trajec- tories taking into account levels of education succession constitutes an integrated parallel consecutive process of achieving educational results, which is also focused on the requirements of a specific professional standard. The advantage of the practice-oriented educational paradigm has been substantiated. It has been revealed that competences are a result of education regardless of trajectories and/or ways of acquiring knowledge, abilities and skills, which promotes mobility of the workforce.